NiMoV and NiO-based catalysts for efficient solar-driven water splitting using thermally integrated photovoltaics in a scalable approach - İlknur Bayrak Pehlivan; Johan Oscarsson; Zhen Qiu; Lars Stolt; Marika Edoff; Tomas Edvinsson (iScience, 2021)
Summary: In this work, a trimetallic NiMoV catalyst is developed for the hydrogen evolution reaction and characterized with respect to structure, valence, and elemental distribution. The overpotential to drive a 10 mA cm−2 current density is lowered from 94 to 78 mV versus reversible hydrogen electrode by introducing V into NiMo. A scalable stand-alone system for solar-driven water splitting was examined for a laboratory-scale device with 1.6 cm2 photovoltaic (PV) module area to an up-scaled device with 100 cm2 area. The NiMoV cathodic catalyst is combined with a NiO anode in alkaline electrolyzer unit thermally connected to synthesized (Ag,Cu) (In,Ga)Se2 ((A)CIGS) PV modules. Performance of 3- and 4-cell interconnected PV modules, electrolyzer, and hydrogen production of the PV electrolyzer are examined between 25°C and 50°C. The PV-electrolysis device having a 4-cell (A)CIGS under 100 mW cm−2 illumination and NiMoV-NiO electrolyzer shows 9.1% maximum and 8.5% averaged efficiency for 100 h operation.